2019
DOI: 10.1021/acs.oprd.9b00248
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Alkene Difunctionalization Reactions of Enolates for the Synthesis of Substituted Bicyclic Cyclopentanes

Abstract: Palladium-catalyzed alkene difunctionalization reactions between alkenes bearing tethered aryl or alkenyl triflates and enolate nucleophiles are described. The transformations form two C−C bonds, a ring, and up to two stereocenters while producing substituted cyclopentane derivatives that contain appended carbonyl functionality. Products are formed with up to >20:1 diastereoselectivity, and the formation of sterically congested bonds between quaternary carbon atoms is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…With only slight modifications to our reaction conditions (use of LiHMDS as base instead of an alkoxide), ketone and ester enolates proved to be suitable nucleophiles in alkene difunctionalization reactions of 22. [22] Low yields of 23 were obtained with methyl ketones or acetate esters (e. g., 23 a) due to competing Pd-catalyzed C-arylation or -alkenylation of the starting material. [19a] However, products 23 were generated in good to excellent yields with mono-or di-substituted ketones or esters.…”
Section: Reactions Of Ketone and Ester Enolatesmentioning
confidence: 99%
“…With only slight modifications to our reaction conditions (use of LiHMDS as base instead of an alkoxide), ketone and ester enolates proved to be suitable nucleophiles in alkene difunctionalization reactions of 22. [22] Low yields of 23 were obtained with methyl ketones or acetate esters (e. g., 23 a) due to competing Pd-catalyzed C-arylation or -alkenylation of the starting material. [19a] However, products 23 were generated in good to excellent yields with mono-or di-substituted ketones or esters.…”
Section: Reactions Of Ketone and Ester Enolatesmentioning
confidence: 99%
“…We recently described a new Pd-catalyzed cross-coupling (alkene difunctionalization) reaction between nitrile nucleophiles and 2-allylphenyl triflate derivatives or related alkenyl triflates. During the course of these studies, we found that transformations of relatively bulky α-branched nitriles were generally effective (Scheme , eq 1). However, yields decreased as the size of the alkyl chain decreased, with competing direct α-arylation of the nitrile becoming increasingly problematic.…”
mentioning
confidence: 99%
“…Our group recently reported a new method for the synthesis of indane derivatives bearing ester, ketone, or malonate groups through Pd-catalyzed cross-coupling (alkene difunctionalization) reactions of enolate nucleophiles with 2-allylphenyl triflate derivatives or related alkenyl triflates. In a representative example, the Pd/BrettPhos-catalyzed coupling of 1a with diethyl malonate afforded a 93% yield of substituted indane product 2a (Scheme , eq 1) . However, when ethyl cyanoacetate was used in place of diethyl malonate, only trace formation of product 2b was observed.…”
mentioning
confidence: 99%